“A Mirror for Men” – Reconstructing a Medieval Polishing Bench and Putting it to the Test - Florian Messner (EXARC, 2020)
In the late 5th century AD, the famous Ostrogoth Theoderic the Great received a truly regal gift from the king of the Warini: he was given highly elaborated swords, richly decorated and able to cut through armour. Their fullers (long grooves along the flat side of the blade to reduce weight and to gain stability, often falsely called “blood groove”) were so well made it was as if worms (or dragons) were crawling upon the surface. But the most outstanding feature was indeed the surface of the blades, which were so expertly polished as if to create “a mirror for men”. To prove that this description of the quality of medieval swords wasn’t an exaggeration I was granted funding by the Tyrolean Scientific Fund (TWF) to reconstruct a medieval polishing bench and to examine possible historical abrasive agents.